The electrochemical reaction mechanism of arsenic deposition on an Au(111) electrode - Jia, Z; Simm, A; Dai, X; Compton, R (2006)
The cyclic voltammograms and linear sweep voltammograms of arsenic deposited on an Au(1 1 1) electrode were measured in a phosphate buffer (pH 1.0) containing 0.1 mM NaAsO2 under IR compensation mode in order to gain an insight into the mechanism of arsenic deposition and stripping at an Au(1 1 1) surface. The amount of arsenic deposit is determined to be approximately one monolayer by calculating the charge of anodic stripping peak of the linear sweep voltammograms. The rate of deposition decreases as the amount of the deposit increases. The analyses reveal that the electrodeposition of arsenic is a totally irreversible electrode reaction and the exchange current density is 6.3 × 10-7 A cm-2. The Tafel plot analyses indicate that the transfer of the first accepted electron is the rate-determining step. © 2005 Elsevier B.V. All rights reserved.